The Rights of Women in International Human Rights Law Textbooks: Segregation, Integration, or Omission? - Farrior, Stephanie (Columbia Journal of Gender and Law, 2003)
Our panel was asked to address the question: whom do feminist law journals serve, and how does that affect the answers to questions of autonomy versus integration? One important role of any student-edited law journal is the pedagogical role, with students as one constituency whom law journals serve. Authors who place articles may end up supplementing the teaching of students who edit the journal. This was the case with the publication of my article on the international law on trafficking in women for prostitution.’ One section of the article dealt with the “due diligence” standard for assessing when the state may be held responsible for the human rights abuses by non-state actors. This is the standard used, for example, in the United Nations (UN) Declaration on Violence against Women,2 and in the sections on violence against women in the Declaration and Platform for Action adopted at the UN Fourth World Conference on Women in Beijing in 1995.3 When I got my edited draft back from the journal with which I had placed it, every reference to the term “due diligence” had been stripped from the article and replaced with such phrases as “diligently” and “with diligence.” It was apparent that if the student editor had taken a human rights or international law course, the student had not been exposed to one of the most important principles i n t he p rotection o f t he human rights o f women. Although the journal involved was an international human rights journal, not a feminist law journal, colleagues have had similar experiences with their articles in women and the law journals. It is apparent that such journals provide a forum and opportunity for students to become familiar with aspects of human rights law that they may not learn about elsewhere.